A Case Study to Explore IoT Readiness in Outbound Logistics - Hasan, Mohd Hilmi; Khairuddin, Aimi Amirah; Akhir, Emelia Akashah Patah (ExcelingTech, 2019)
Most of the logistics companies are facing problems with tracking and tracing in their logistics networks that led to poor last-mile service quality. This problem can be solved by improving technology such as the Internet of Things (IoT). Midway through the second decade of the millennium, the rapid development of IoT has influenced the company’s outbound logistics operations such as last-mile delivery. Implementation of IoT will help courier companies to optimize their delivery process. Despite its popular perceived benefit in assisting last-mile delivery, IoT remains a new technology and its adoption rate is still low in Malaysia. Thus, the main purpose of this research is to explore the status of IoT readiness among logistics companies in Malaysia. Apart from that, this research also intends to propose the best practice for courier companies to implement IoT. The finding of this research will indicate the factors affecting the readiness of the organizations to adopt IoT and the best practice for the implementation of IoT for the last-mile of a parcel delivery service in Malaysia will be proposed. This research is carried out by making use of qualitative methods with a number of courier companies in Malaysia as case studies. The case study provided is related to a courier company in Malaysia. In the preliminary study phase, results show that IoT helps to improve productivity and enhance the efficiency of the company.